Personal and Workgroup Incivility: Impact on work and Health Outcomes - LIM, Sandy (Institutional Knowledge at Singapore Management University, 2008)
This article develops a theoretical model of the impact of workplace incivility on employees' occupational and psychological well-being. In Study 1, the authors tested the model on 1,158 employees, finding that satisfaction with work and supervisors, as well as mental health, partially mediated effects of personal incivility on turnover intentions and physical health; this process did not vary by gender. Study 2 cross-validated and extended these results on an independent sample of 271 employees, showing negative effects of workgroup incivility that emerged over and above the impact of personal incivility. In both studies, all results held while controlling for general job stress. Implications for organizational science and practice are discussed.